2014
DOI: 10.1021/la4044254
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Test for Ice Adhesion Strength Using Commercial Instrumentation

Abstract: A laboratory test method for evaluating ice adhesion has been developed employing a commercially available instrument normally used for dynamic mechanical analysis (TA RSA-III). This is the first laboratory ice adhesion test that does not require a custom-built apparatus. The upper grip range of ∼10 mm is an enabling feature that is essential for the test. The method involves removal of an ice cylinder from a polymer coating with a probe and the determination of peak removal force (Ps). To validate the test me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 41 publications
3
76
0
Order By: Relevance
“…17 The glass transition temperature for PMMA is ∼110°C higher than the ice removal test. This test case may be described as removal of a rigid object (ice) from a rigid substrate (a glass).…”
Section: ■ Results and Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…17 The glass transition temperature for PMMA is ∼110°C higher than the ice removal test. This test case may be described as removal of a rigid object (ice) from a rigid substrate (a glass).…”
Section: ■ Results and Discussionmentioning
confidence: 90%
“…5 Our previous work showed that the effect of probe speed was negligible for P s measurements on the polymer glass PMMA. 17 Probe speed dependence was explored for Sylgard 184 coatings having thicknesses noted above. Figure 6A shows P s vs 1/t 1/2 for three probe speeds: 0.1, 0.05, and 0.025 mm/s.…”
Section: Focusing Inmentioning
confidence: 99%
See 3 more Smart Citations